Reversible right bundle branch block caused by spasm of the anterior septal branch: case report - Yue Bao; Hongwei Yi; Jun Ma (BMC Cardiovascular Disorders)
Abstract Background Coronary Artery Spasm (CAS) often presents in the epicardial coronary arteries. The anterior septal branch is distributed within the myocardium, and occurrences of spasms are rare. Currently, there is no available literature on this topic, and the onset of symptoms remains elusive, potentially leading to misdiagnosis. Case presentation We present a case of acute myocardial infarction (AMI) caused by spasm in the anterior septal branch, accompanied by transient right bundle branch block (RBBB). The administration of nitroglycerin via intracoronary injection resulted in the alleviation of spasm in the anterior septal branch and the disappearance of RBBB. After the administration of anti-coronary spasm medications, the patient exhibited favorable recovery outcomes. No episodes of myocardial ischemia were observed during the six-month follow-up. Conclusions The presence of new RBBB in patients may warrant consideration of anterior septal coronary artery spasm, which necessitates urgent coronary angiography to clarify the underlying cause and facilitate the prompt initiation of anti-spasm treatment.